2016
DOI: 10.1073/pnas.1521846113
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Bcl11b sustains iNKT1 and iNKT2 cell programs, restricts iNKT17 cell program, and governs iNKT cell survival

Abstract: Invariant natural killer T (iNKT) cells are innate-like T cells that recognize glycolipid antigens and play critical roles in regulation of immune responses. Based on expression of the transcription factors (TFs) Tbet, Plzf, and Rorγt, iNKT cells have been classified in effector subsets that emerge in the thymus, namely, iNKT1, iNKT2, and iNKT17. Deficiency in the TF Bcl11b in double-positive (DP) thymocytes has been shown to cause absence of iNKT cells in the thymus and periphery due to defective self glycoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…3c). Genes that were downregulated in Tet2-Tet3 DKO stage 0 i NKT precursors relative to their expression in wild-type cells included those encoding CD4, Bcl11b (which restricts the NKT17 lineage 23 ) and Satb1 (which forms complexes with PLZF in the presence of the Cullin E3 ligase 24 ); genes that were upregulated included Zbtb16 (which encodes PLZF) and Lmo4 (Fig. 3c).…”
Section: Resultsmentioning
confidence: 99%
“…3c). Genes that were downregulated in Tet2-Tet3 DKO stage 0 i NKT precursors relative to their expression in wild-type cells included those encoding CD4, Bcl11b (which restricts the NKT17 lineage 23 ) and Satb1 (which forms complexes with PLZF in the presence of the Cullin E3 ligase 24 ); genes that were upregulated included Zbtb16 (which encodes PLZF) and Lmo4 (Fig. 3c).…”
Section: Resultsmentioning
confidence: 99%
“…6b ). The transcription factors Bcl11b and Lef1 restrain the differentiation of iNKT17 cells as iNKT cells deficient for either transcription factor had increased frequencies of ROR-γt expressing iNKT17 cells 27 , 29 . Interestingly, in PLZF-cre Runx1 cKO mice, there was a statistically significant increased expression of both Bcl11b (2 fold) and Lef1 (2 fold) in Stage 2 iNKT cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While BATF, c-Maf and NKAP positively regulate iNKT17 differentiation; the transcription factors Bcl11b and Lef1 restrain iNKT17 differentiation. Deficiency in either factor in iNKT cells led to an increased frequency of iNKT17 cells 27 , 29 . Although, Runx1 can induce rorc expression and associate with ROR-γt during Th17 differentiation 39 , its role in iNKT17 differentiation has not been defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in support of thymic commitment it has been shown that the TCR signal strength during thymic development can direct the differentiation of iNKT cells within specific functional subsets . Further to this, a variety of signalling molecules and transcription factors including Zap70, Bcl11b or Roquin has been shown to participate in the control of iNKT cell lineage differentiation . On the other hand, several lines of evidence suggest that iNKT cells can acquire functional capabilities in the periphery.…”
Section: Nkt Cells: An Overviewmentioning
confidence: 99%